Exile in the Maghreb Jews under Islam, sources and documents, 997-1912 - Fenton, Paul; Littman, David 1933-2012 (Fairleigh Dickinson University Press, 2016)
The Exile in the Maghreb entails the first attempt at describing the historical reality of the legal and social condition of the Jews in the Muslim countries of North Africa (principally Algeria and Morocco) over a thousand year period from the Middle Ages (997 C.E.) to the French colonization (1830 Algeria/1912 Morocco.). The Exile is not a formal history but a chronological anthology of documents drawn from literary (section A) and archival sources (section B), many of which are published for the first time